Associations of Bone Mineral Density and Bone Metabolism Indices with Urine Albumin to Creatinine Ratio in Chinese Patients with Type 2 Diabetes - Zhao, Xin; Zhang, Xiao-Mei; Yuan, Ning; Yu, Xiao-Feng; Ji, Li-Nong (Experimental and Clinical Endocrinology & Diabetes, 2019)
Objective To identify correlations of bone mineral density (BMD) and bone metabolism indices with the urine albumin to creatinine ratio (ACR) as an indicator of nephropathy in Chinese patients with type 2 diabetes (T2D).Methods In this retrospective analysis, 297 patients with T2D were divided into 3 groups according to the urine ACR. Patients’ data were analyzed to identify associations of general conditions, blood glucose level, lipid levels, and uric acid level with BMD and bone metabolism indices.Results BMD at every location tested (femoral neck, trochanter, inside hip, Ward’s triangle, total hip, and lumbar vertebrae) was negatively correlated with the urine ACR (all p<0.05). Osteocalcin, beta-C-terminal telopeptide (β-CTX), and procollagen type 1 N- peptide (P1NP) were positively correlated with urine ACR (all p<0.05). Finally, 25-hydroxyvitamin D [25(OH)D] was negatively correlated with urine ACR (p<0.05). Multiple regression analysis with adjustment for age, body mass index, disease duration, and other clinical measurements revealed no significant correlation between urine ACR and BMD measurements or β-CTX (p>0.05). However, significant correlations remained between urine ACR and osteocalcin, P1NP, and 25(OH)D (p<0.05). The same results were obtained for postmenopausal women specifically, with the exception of a significant correlation between the ACR and β-CTX (p<0.05).Conclusion In the early stage of diabetic nephropathy, BMD changes and bone transformation acceleration may occur, and the acceleration of bone transformation may occur before the change in BMD. Therefore, it is important to monitor bone metabolism indices in the early stage of diabetic nephropathy in T2D patients.
Keywords: type 2 diabetes mellitus; osteoporosis; BMD; ACR